ANALISIS DISIPLIN KERJA APARATUR SIPIL NEGARA PADA KANTOR BADAN PENGELOLA KEUANGAN DAN ARSIP DAERAH KOTA SAMARINDA - Nita Rahma Wati (ADMINISTRASI PUBLIK, 2019)
Discipline is the training of one's awareness to comply with regulations in the absence of forced elements so as to produce attitudes and control of habits for the organization in achieving a goal. This research was conducted at the BPKAD office in the city of Samarinda. Especially for BPKAD office employees in the city of samarinda. The purpose of this study was to determine the analysis of the factors that influence the work discipline of employees at the BPKAD office in the city of Samarinda.The use of samples in this study, the authors apply the sample is the whole of the population. As for the method of data collection is the census technique that is the population that can be considered as representing all employees. The sample in this study were 87 people.Data collection techniques used are primary and secondary. The analysis used is descriptive qualitative, namely analyzing the data obtained based on reality and then connected with the theories that support the discussion, then the authors draw some conclusions from these explanations.From the results of the study it can be concluded that leadership, penalties and motivational sanctions can affect discipline. In this case the author suggests that in improving the discipline of work pegawaai, leaders must be more assertive in giving sanctions to employees who violate the rules do not be at the office at the time of official work hours are still ongoing and always pay attention to the attendance of employees at the BPKAD office in Samarinda city and management can be created and done.